RETRACTED: Analysis of the Ratio of Effectiveness and Efficiency of Local Original Income of West Bandung Regency for the 2018-2022 Period - Ravlina Aisyah Mahri; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research focuses on effectiveness and efficiency analysis in managing local revenue in West Bandung Regency for the 2018-2022 period. Furthermore, this research adopts a quantitative descriptive method to analyze the variables used: the ratio of effectiveness and efficiency. Based on the findings and calculations, especially on the effectiveness ratio variable, the West Bandung Regency regional government is categorized as quite effective in managing its original regional income with an average gain of 90.98%. The efficiency ratio variable shows that the West Bandung Regency regional government is categorized as inefficient in managing regional original income, where the average acquisition was found at 103.4%. Thus, the effectiveness ratio aspect is reasonably practical. It needs to be improved in the future. The efficiency ratio of the West Bandung Regency regional government needs to adjust its original regional income properly in the future so that the budget used can be more efficient with management that is right on target.